Characterizing the indigenous forest peoples of Latin America: Results from census data. (January 2020) - Thiede, Brian C.; Gray, Clark
Highlights: Non-indigenous forest-dwellers outnumber indigenous forest peoples (IFPs) by more than eight to one. IFPs have lower fertility than their non-indigenous counterparts net of other characteristics. Most in-migrants to forested areas are non-indigenous and settle in forested areas with few indigenous inhabitants. Results support arguments for strengthening services in remote forest settlements and empowering IFPs more broadly. Abstract: Indigenous populations in Latin America are central to regional and global efforts toward achieving socially and environmentally sustainable development. However, existing demographic research on indigenous forest peoples (IFPs) has many limitations, including a lack of comparable cross-national evidence. We address this gap by linking representative census microdata to satellite-derived tree cover estimates for nine countries in the region. Our analyses describe the demographic and socioeconomic characteristics of IFPs, and draw comparisons with reference groups. Our first goal is to examine within- and between-population variation in the age structure, human capital attainment, and economic status of IFPs. We then analyze patterns of fertility among indigenous forest-dwelling women and comparison groups. Finally, we examine the association between migration patterns and tree cover among indigenous and non-indigenous populations. Findings demonstrate that Latin America's IFPs are materially deprived and characterized by high fertility levels overall. Importantly for sustainable development efforts, we show that non-indigenous forest-dwellers outnumber IFPs by more than eight to one and that IFPs have lower fertility than their non-indigenous counterparts when other characteristics are accounted for. Additionally, we find that most in-migrants to heavily-forested areas are non-indigenous, and that in-migrants tend to settle in areas that are forested but have few indigenous inhabitants. These results provide new cross-national evidence on the state of IFPs in Latin America, and highlight the need to empower these groups in the face of growing social and environmental crises in the region.